Scaling up community-driven development: a synthesis of experience - Gillespie, Stuart (International Food Policy Research Institute, 2005)
While many community-driven development (CDD) initiatives may be successful, their impact is often limited by their small scale. Building on past and ongoing work on CDD, this study addresses the fundamental question: how can CDD initiatives motivate and empower the greatest number of communities to take control of their own development? What are the key contextual factors, institutional arrangements, capacity elements, and processes related to successful scaling-up of CDD, and, conversely, what are the main constraints or limiting factors, in different contexts? Drawing upon recent literature and the findings from five case studies, key lessons on how best to stimulate, facilitate, and support the scaling-up of CDD in different situations, along with some major challenges, are highlighted. Lessons include the need for donors and supporters of CDD, including governments, to think of the process beyond the project, and of transformation or transition rather than exit. Donor push and community pull factors need to be balanced to prevent "supply-driven, demand-driven development.